2016
DOI: 10.1002/cne.24119
|View full text |Cite
|
Sign up to set email alerts
|

Akinesia and freezing caused by Na+ leak‐current channel (NALCN) deficiency corrected by pharmacological inhibition of K+ channels and gap junctions

Abstract: The Na leak-current channel (NALCN) regulates locomotion, respiration, and intellectual development. Previous work highlighted striking similarities between characteristic movement phenotypes of NALCN-deficient animals (Drosophila and Caenorhabditis elegans) and the major symptoms of Parkinson's disease and primary progressive freezing gait. We have discovered novel physiological connections between the NALCN, K channels, and gap junctions that mediate regulation of locomotion in C. elegans. Drugs that block K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Using a C . elegans model mimicking IHPRF, it was recently suggested that NALCN deficiency may be corrected by pharmacological targeting of other channels 58 . Conversely, one may predict that partial inhibition of NALCN could present some benefits for CLIFAHDD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Using a C . elegans model mimicking IHPRF, it was recently suggested that NALCN deficiency may be corrected by pharmacological targeting of other channels 58 . Conversely, one may predict that partial inhibition of NALCN could present some benefits for CLIFAHDD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we used a χ 2 test to evaluate whether differences between the treatment groups and the controls were statistically significant. We have previously employed the same statistical approach for the analysis of spontaneous movement in other strains [23]. The χ 2 method does not generate standard deviations.…”
Section: Methodsmentioning
confidence: 99%
“…At various times after transfer, we observed the animals individually for 5 s and scored them as “spontaneously moving” if they traveled more than 2 head lengths (about half their body length) in either direction as described elsewhere [23]. All incubation steps and observations were performed at 25°C or room temperature, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the routine use of a homozygosity data mapping algorithm might be helpful for improving the diagnostic yields of next‐generation sequencing without requiring the addition of an SNP array analysis. Recent loss‐of‐function studies for Nalcn in model organisms have suggested that neurological symptoms can be alleviated by the voltage gated K+ channel inhibitor 4‐aminopyridine (Kasap, Bonnett, Aamodt, & Dwyer, ). A precise diagnosis of this condition could have potential therapeutic implications.…”
Section: Discussionmentioning
confidence: 99%